2007
DOI: 10.1021/jo070731i
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Microwave-Assisted Amination of 2-Chloro-5-nitrobenzoic Acid

Abstract: The synthesis of N-substituted 5-nitroanthranilic acid derivatives 3a-w was achieved by a new, mild, microwave-assisted, regioselective amination reaction of 5-nitro-2-chlorobenzoic acid (1a) with a diverse range of aliphatic and aromatic amines 2a-w without added solvent or catalyst. Up to >99% isolated yield was obtained within 5-30 min at 80-120 degrees C. The reaction, which is suitable for upscaling, yielded new compounds that are of considerable interest as useful building blocks and as potential drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The syntheses of compounds 5, 7-10, 15-20, 22-25, 27-29, 31-43, 46, and 49 have previously been described. 32,34,35 21,26,30,47,50, and 53-55, whose syntheses had previously been described by classical methods, 35,[39][40][41][42][43][44][45][46][47][48] as well as the new compounds 11,44,45,48,51,52, and 56-60 were obtained in analogy to a new method recently developed by our group applying a simple and efficient microwave-assisted Ullmann reaction (Scheme 1). 49 Our experiments showed that a wide variety of amines (aliphatic and aromatic) including highly electron-deficient ones could be smoothly coupled with anthraquinone halide derivatives 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The syntheses of compounds 5, 7-10, 15-20, 22-25, 27-29, 31-43, 46, and 49 have previously been described. 32,34,35 21,26,30,47,50, and 53-55, whose syntheses had previously been described by classical methods, 35,[39][40][41][42][43][44][45][46][47][48] as well as the new compounds 11,44,45,48,51,52, and 56-60 were obtained in analogy to a new method recently developed by our group applying a simple and efficient microwave-assisted Ullmann reaction (Scheme 1). 49 Our experiments showed that a wide variety of amines (aliphatic and aromatic) including highly electron-deficient ones could be smoothly coupled with anthraquinone halide derivatives 6.…”
Section: Resultsmentioning
confidence: 99%
“…The syntheses of compounds 5, 7-10, 15-20, 22-25, 27-29, 31-43, 46, 49, 50, 53, 62, and 63 were previously described. 32,33,35,48,49 All other compounds were newly prepared in analogy to the described method. 49 General Procedure.…”
Section: Methodsmentioning
confidence: 99%
“…There were three aromatic proton signals also observed in the NMR spectrum of functionalized PMMA. The NMR signal at 7.134 ppm was observed for H d of aromatic ring while signals at 7.829 and 8.210 ppm were observed for H e and H f of aromatic ring . The shifting in the δ values of these signals was observed due to presence of highly electronegative moieties (electron withdrawing group) in neighbor of these protons.…”
Section: Resultsmentioning
confidence: 95%
“…The precipitated solid was filtered off, washed with distilled water (3×20 mL) and re-crystallised from ethanol/water to give the desired product with the yields listed in Tables 2 and 3. 13 …”
Section: Amination Of 2-chloro-5-nitrobenzoic Acid In Superheated Water;mentioning
confidence: 99%